menu
QAmmunity.org
Login
Register
My account
Edit my Profile
Private messages
My favorites
Register
Ask a Question
Questions
Unanswered
Tags
Categories
Ask a Question
Original equation: 3(a-2) + 14 =8-6a Solution: 3a-2+14-8-6a 3a +12=8-6a 9a + 12 = 8 9a = -4 a = -4/9
asked
Sep 25, 2024
72.9k
views
2
votes
Original equation:
3(a-2) + 14 =8-6a
Solution: 3a-2+14-8-6a
3a +12=8-6a
9a + 12 = 8
9a = -4
a = -4/9
Mathematics
high-school
Panupan
asked
by
Panupan
7.1k
points
answer
comment
share this
share
0 Comments
Please
log in
or
register
to add a comment.
Please
log in
or
register
to answer this question.
1
Answer
2
votes
so what do you need help with
JConstantine
answered
Oct 1, 2024
by
JConstantine
7.0k
points
ask related question
comment
share this
0 Comments
Please
log in
or
register
to add a comment.
Ask a Question
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.
8.3m
questions
10.9m
answers
Other Questions
How do you can you solve this problem 37 + y = 87; y =
What is .725 as a fraction
How do you estimate of 4 5/8 X 1/3
A bathtub is being filled with water. After 3 minutes 4/5 of the tub is full. Assuming the rate is constant, how much longer will it take to fill the tub?
Write words to match the expression. 24- ( 6+3)
Twitter
WhatsApp
Facebook
Reddit
LinkedIn
Email
Link Copied!
Copy
Search QAmmunity.org